Biogas. Issue 5 (14th September 2017) - Plugge, Caroline M.
Summary: Biogas production represents a fascinating process for the recovery of nutrients and renewable energy from various organic waste streams. The process is of interest for the production of value‐added chemicals by mixed cultures and can also be applied in combined bioenergy production systems. Strategies and opportunities for optimization of biogas quality and quantity are presented.